1998
DOI: 10.1021/jp982174x
|View full text |Cite
|
Sign up to set email alerts
|

Congruent Vaporization of Solid Manganese Monotelluride and the Effects of Phase Transitions:  A High-Temperature Mass Spectrometric Study

Abstract: Vaporization studies on Mn-Te samples of initial compositions 49.6 and 54.9 at. % Te were conducted by Knudsen effusion mass spectrometry. Both these samples on continuous vaporization reached the congruently effusing compositions (CECs) ≈ 50 at. % Te. Vaporization chemistry around this composition was studied from 1194 to 1343 K to examine the effects associated with the reported phase transitions in MnTe(s) at 1228 (R T β), 1293 (β T γ), and 1323 K (γ T δ). Among these, only the R T β phase transition showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 17 publications
1
24
1
Order By: Relevance
“…(20) In the case of MnTe, assigning the stoichiometric composition for its Te-rich boundary (c = 1) at 650 K < T < 750 K may not be seriously incorrect, if we draw upon an inference from our previous study (9) of its congruently effusing composition (CEC): with decrease in temperature, the x(Te) corresponding to the CEC would decrease from the value of (0.492 ± 0.011) determined at 1194 K T 1223 K, and the Te-rich boundary, not far from it, may well have x(Te) ≈ 0.5. Nevertheless, we chose x(Te) = 0.507, which corresponds to a value of c = 1.03 deduced from the results given by Abrikosov et al (17) and Furberg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(20) In the case of MnTe, assigning the stoichiometric composition for its Te-rich boundary (c = 1) at 650 K < T < 750 K may not be seriously incorrect, if we draw upon an inference from our previous study (9) of its congruently effusing composition (CEC): with decrease in temperature, the x(Te) corresponding to the CEC would decrease from the value of (0.492 ± 0.011) determined at 1194 K T 1223 K, and the Te-rich boundary, not far from it, may well have x(Te) ≈ 0.5. Nevertheless, we chose x(Te) = 0.507, which corresponds to a value of c = 1.03 deduced from the results given by Abrikosov et al (17) and Furberg.…”
Section: Discussionmentioning
confidence: 99%
“…As part of our program to obtain such information, we have conducted high-temperature mass spectrometric investigations on tellurides of Fe, (1,2) Cr, (3,4) Ni, (5) Mo, (6,7) and Mn. (8,9) In the (manganese + tellurium) system, our previous studies both revolved around the manganese monotelluride phase: determination of the composition and thermodynamic properties corresponding to the Mn-rich phase boundary; (8) and investigation of vaporization behavior during congruent vaporization and condensed-phase transitions. (9) The present work concerns manganese ditelluride, the only other phase known to exist in the (manganese + tellurium) system.…”
Section: -9614/02mentioning
confidence: 99%
See 1 more Smart Citation
“…The mass spectrometric investigation by Lakshmi Narasimhan et al (12) confirmed that the atomic fractions of Mn and Te in the condensed phase are constant, and thus vaporization is congruent. During congruent vaporization,…”
Section: Mn/te Systemmentioning
confidence: 93%
“…Such effects are better understood now after sustained research on this topic. (3)(4)(5)(6)(7)(8)(9)(10)(11)(12) Suppose a congruently vaporizing two-component condensed phase A x B (1−x) (CP1) transforms upon a temperature change to another congruently vaporizing condensed phase A y B (1−y) (CP2) within an effusing or transpiring system in which the rate of vapor loss is arbitrarily slow such that equilibrium obtains. For a three-phase equilibrium involving vapor, CP1, and CP2, the conservation of matter requires that compositions of all the three phases be different.…”
Section: Introductionmentioning
confidence: 99%